An effective strategy to boost the robustness of metal–organic frameworks via introduction of size-matching ligand braces. Issue 9 (21st December 2015) - Wang, Xiuli; Gao, Wen-Yang; Luan, Jian; Wojtas, Lukasz; Ma, Shengqian
Abstract : The introduction of size-matching ligand braces has been illustrated as an effective strategy to boost the robustness of MOFs. Abstract : Framework fragility upon the removal of guest solvent molecules has remained an issue for a substantial amount of metal–organic frameworks (MOFs). To address this issue, in this work we illustrate a strategy for the introduction of size-matching ligands as braces that are deliberately anchored onto the open metal sites to support and segment the pores thereby boosting the framework robustness. This is exemplified by employing 4, 4′-bipyridine as a brace to bridge two trigonal prismatic clusters of Co3 (μ3 -O)(COO)6, generating a robust MOF that exhibits permanent porosity and selective gas adsorption behaviors.